Response on S Memon, et al. (J Pak Med Assoc. 74: 1163-1166, June 2024) Osmolar gap in hyponatraemia: An exploratory study - Shoukat Memon,; Faiza Saeed,; Ashar Alam,; Javeria Chughtai,; Salman Imtiaz, (Journal of the Pakistan Medical Association, 2025)
Thank you very much for your insightful comments,which will certainly enhance the clarity and highlight theimportance of this topic. Our study revealed a notablenumber of patients with elevated osmolar gap (OG), withdiabetes being the third most common comorbidity afterCKD and hypertension. Addressing the influence of bloodglucose on OG is indeed essential; however, due tojournal limitations, I was unable to include the tableshowing the Mean ± SD of RBS (mg/dl) in the Raised OGgroup (n=141) at 153.94 ± 72.53 and in the Normal OGgroup (n=121). Notably, no cases of DKA were identified.I acknowledge that this aspect, along with otherlimitations—such as the lack of measurements for totallipids, total protein, and serum lactate—was notthoroughly addressed in our study. These variables wereinitially excluded due to the study’s primary focus onhyponatraemia, its severity, and outcomes. The discoveryof elevated OG in a substantial number of patientsbecame evident later in the research, prompting us toobtain IRB approval to include OG measurements. Mygoal was to emphasize this significant finding, which hasnot been widely recognized, and I encourage furtherresearch to investigate this area more comprehensively.